2004
DOI: 10.1016/j.intcom.2004.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Employing think-aloud protocols and constructive interaction to test the usability of online library catalogues: a methodological comparison

Abstract: This paper describes a comparative study of three usability test approaches: concurrent thinkaloud protocols, retrospective think-aloud protocols, and constructive interaction. These three methods were compared by means of an evaluation of an online library catalogue, which involved four points of comparison: number and type of usability problems detected; relevance of the problems detected; overall task performance; and participant experiences. The results of the study showed that there were only few signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 18 publications
4
53
1
1
Order By: Relevance
“…Comparing the two protocols in terms of whether they identify the same problems, we found that only 27 % of the distinct problems were identified by both protocols. Van den Haak et al [25][26][27][28]] also compared overlap between the two protocols in their studies. The overlap in most of the studies [25][26][27] was similar with the overlap reported in the study here, except for one study [28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparing the two protocols in terms of whether they identify the same problems, we found that only 27 % of the distinct problems were identified by both protocols. Van den Haak et al [25][26][27][28]] also compared overlap between the two protocols in their studies. The overlap in most of the studies [25][26][27] was similar with the overlap reported in the study here, except for one study [28].…”
Section: Discussionmentioning
confidence: 99%
“…Van den Haak et al [25][26][27][28]] also compared overlap between the two protocols in their studies. The overlap in most of the studies [25][26][27] was similar with the overlap reported in the study here, except for one study [28]. Unfortunately, van den Haak et al did not specifically report the overlap between CVP and RVP, as they included other protocols in their studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations